TD 4. Sustainable spawns and pure cultures of selected edible mushrooms using coconut (AROD, LAGT, & MRD) ligno-cellulosic media (2018)
The study gives emphasis on generating novel coconut-based technology for mushroom cultivation to address the issue on food security where current practice utilizes substantial volume of grains as media for mushroom. Sustainable resources from coconut wastes generated from plantation areas, buko stores, and from hybridization program were evaluated as culture media substitutes. The fresh and spent coconut male flower of Laguna tall (LAGT), Malayan Red Dwarf (MRD), and spent Aromatic Green Dwarf (AROD) were evaluated as nutrient substitute to potato in producing Potato Sucrose Agar (PSA). The mycelial growth rates (MGR) were determined by taking the radius of mycelia grown in agar media in cm/day. The MGR of Lentinus edodes are both higher in LAGT and MRD vs. PSA. There is no significant difference however among the MGRs of PSA, MRD, and LAGT for milky mushroom. In addition, there is no significant difference at p<0.05 using Least Significant Difference (LSD) test in the MGR of Hypsizygus tessellatues in PSA, MRD, and LAGT. The dry weight of mycelia recorded the highest in MRD and LAGT fresh and spent male flowers as compared to PSA and AROD husk. Furthermore, spawn production of Pleurotus eryngii, Calocybe indica, and Hypsizygus tessellatues obtained the fastest colonization in coconut spikelets. Sorghum and Coconut male flowers are better substrates in shitake spawn production. In conclusion, coconut waste substrates are good alternatives for crop-based media in mushroom spawn and pure culture production especially now that climate change is bringing disruption in the global food production. Furthermore, the results of this study shall also pave way to coconut waste management and novel product development. Furthermore, the results of this study shall also pave way to coconut waste management and novel product development.